Looking for the most effective combinations of inhaled drugs in asthma and COPD - Szmidt, Mirosław (Przewodnik Lekarza/Guide for GPs, 2010)
The treatment of asthma with inhaled glucocorticosteroids and long-acting beta-2 adrenergic agonists (LABA) in one inhaler as a maintenance therapy and as needed, is a strategy which diminishes inflammation and controls asthma symptoms. Large, randomized double-blind clinical trials show that budesonide/formoterol (Symbicort, AstraZeneca) applied in this way improve the control of symptoms, diminish the number of exacerbations and allow to decrease the doses at lower costs. It is confirmed by recently published studies which compare such a way of treatment with the best conventional therapy. Chronic obstructive pulmonary disease (COPD) has been considered to be more stable and with less variable symptoms than asthma. In many patients with COPD the morning is the worst time of the day when patients often experience the most severe CPOD symptoms and limitation of simple, morning everyday activities . Two questionnaires for assessing symptoms and the capacity of performing simple everyday activities have been published. The studies using these questionnaires showed that 73% patients with severe COPD have problems with washing, drying, getting dressed, putting on shoes and socks. Budesonide/formoterol- treated COPD patients benefited more from rapid improvement in performing simple morning activities than the ones treated with fluticasone/salmeterol. Adding tiotropium – an anti-muscarinic drug to budesonide/formoterol diminished the number of exacerbations, improved the lung function, lowered the number of inhalations of relievers, and improved the patient’s performance of simple morning routines. Doctors should pay more attention to symptoms and limitations in simple activities in the morning and adequately adjust the treatment.